Cerebral Erythropoietin Prevents Sex-Dependent Disruption of Respiratory Control Induced by Early Life Stress - Elliot-Portal, Elizabeth; Arias-Reyes, Christian; Laouafa, Sofien; Tam, Rose; Kinkead, Richard; Soliz, Jorge (Frontiers in Physiology, 2021)
Sleep disordered breathing (SDB) is characterized by repeated interruptions of breathing during sleep and a prevalence ~2.5 times greater in men than in women. Early life stress has persistent and sex-specific effects on brain development and outcomes. Disruption of the neural system regulating breathing is an important pathophysiological trait and there is growing evidence in animals and humans that stress may contribute to this in this disorder. Erythropoietin (EPO) is a potent neuroprotector that prevents several conditions associated with hyper-responsiveness of the stress neuroaxis. Here, we tested the hypothesis that EPO prevents sex-specific disruption of respiratory regulation induced by neonatal stress in adult mice. Animals were either raised under standard conditions (controls) or subjected to neonatal maternal separation (NMS; 3h/day from postnatal day 3 to 12). The efficacy of EPO was tested by comparing wildtype mice with transgenic mice that overexpress EPO only in the brain (Tg21). Respiratory function was assessed using whole body plethysmography. Apneas were detected during non-REM sleep; the reflexive responses to stimuli were measured by exposing mice to hypoxia (10% O2; 15 min) and hypercapnia (5% CO2; 10 min). In 7-day-old pups, NMS augmented corticosterone levels only in males; with reduced effect in Tg21. In wildtype, NMS increased the number of apneas and the hypercapnic ventilatory response (HcVR) only in males; with no effect on Tg21. In wildtype males, the incidence of apneas was positively correlated with HcVR and HVR. We conclude that neural EPO effectively reduces stress-induced respiratory disturbances, especially in males.